Intestinal factors promoting the development of RORγt+ cells and oral tolerance - López-Fandiño, Rosina; Molina, Elena; Lozano-Ojalvo, Daniel (Frontiers in Immunology, 2023)
The gastrointestinal tract has to harmonize the two seemingly opposite functions of fulfilling nutritional needs and avoiding the entry of pathogens, toxins and agents that can cause physical damage. This balance requires a constant adjustment of absorptive and defending functions by sensing environmental changes or noxious substances and initiating adaptive or protective mechanisms against them through a complex network of receptors integrated with the central nervous system that communicate with cells of the innate and adaptive immune system. Effective homeostatic processes at barrier sites take the responsibility for oral tolerance, which protects from adverse reactions to food that cause allergic diseases. During a very specific time interval in early life, the establishment of a stable microbiota in the large intestine is sufficient to prevent pathological events in adulthood towards a much larger bacterial community and provide tolerance towards diverse food antigens encountered later in life. The beneficial effects of the microbiome are mainly exerted by innate and adaptive cells that express the transcription factor RORγt, in whose generation, mediated by different bacterial metabolites, retinoic acid signalling plays a predominant role. In addition, recent investigations indicate that food antigens also contribute, analogously to microbial-derived signals, to educating innate immune cells and instructing the development and function of RORγt+ cells in the small intestine, complementing and expanding the tolerogenic effect of the microbiome in the colon. This review addresses the mechanisms through which microbiota-produced metabolites and dietary antigens maintain intestinal homeostasis, highlighting the complementarity and redundancy between their functions.